Folding and unfolding: A topological framework for understanding intangible cultural heritage tourism in urban villages - The case of chebei dragon boat scenery, Guangzhou, China - Xixi Tang; Shengchao Li (PLoS ONE, 2026)
Background Rapid urbanization poses unprecedented challenges to intangible cultural heritage (ICH) preservation, particularly within urban villages where traditional practices face displacement pressures. While heritage tourism offers potential solutions, existing frameworks inadequately address how ICH spaces maintain cultural authenticity while undergoing radical transformation. Methods This study introduces a novel topological framework to analyze ICH space dynamics, conceptualizing them as entities capable of continuous deformation while preserving fundamental properties. Using grounded theory methodology, we conducted 38 in-depth interviews, extensive participant observation, and comprehensive document analysis of the Chebei Dragon Boat Scenery in Guangzhou, China. Results Our analysis reveals a “2-6-18” generative logic underlying ICH space structure and reproduction. We identify “cultural experience” as the core topological invariant that enables cultural continuity despite spatial transformation. ICH spaces are reproduced through dynamic interactions within a “culture-power-capital” three-dimensional matrix, facilitated by tourism-driven “unfolding” processes that make implicit cultural knowledge explicit while maintaining essential properties. Conclusions The findings demonstrate how “urban renewal + cultural tourism integration” can serve as an effective spatial reproduction mechanism for ICH preservation. This topological approach offers a robust analytical framework for heritage tourism management, moving beyond binary preservation-development paradigms toward adaptive sustainability models that honor both cultural continuity and contemporary urban development needs.